Evaluation of reliability and validity of the family adaptability and cohesion evaluation scale (FACES III) among medical students - Tran , Thi Tra My; Nguyen , Thi Phuong Mai; Tran , Binh Thang; Le , Dinh Duong; Dang , Cao Khoa; Nguyen , Bao Tran (Tạp chí Y Dược Huế, 2025)
Background: Family functioning significantly impacts individual mental health, particularly during the transition to university life. While the Family Adaptability and Cohesion Evaluation Scale (FACES III) is a widely used tool to assess family dynamics, its psychometric properties need validation in specific cultural contexts like Vietnam. Objectives: This study aimed to evaluate the reliability and validity of a Vietnamese version of the FACES III scale among medical students. Methods: A cross-sectional study was conducted with 405 medical and preventive medicine students at a medical university. A subset of 106 students participated in a retest evaluation. Reliability was assessed using Cronbach’s alpha and test-retest reliability (Intraclass Correlation Coefficient - ICC). Construct validity was examined using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Data were analyzed using SPSS and AMOS. Results: The initial sample included 405 students (55.6% male). EFA confirmed based on 13 items suggested a three-factor structure explaining 55.6% of the total variance (Factor 1: 7 items, Factor 2: 3 items, Factor 3: 3 items), differing from the original two-factor model. The Kaiser-Meyer-Olkin (KMO) measure was 0.857, and Bartlett’s Test of Sphericity was significant (p < .001), supporting factorability. The overall Cronbach’s alpha for the 13-item revised scale was 0.792. ICC was 0.79, 95%CI [0.71 - 0.86]. CFA indicated acceptable model fit for the threefactor structure (Chi-square/df = 3.331, GFI = 0.926, CFI = 0.898, AGFI = 0.892, RMSEA = 0.076). Conclusion: The revised 13-item, three-factor Vietnamese version of FACES III demonstrated acceptable reliability and construct validity among medical students. This adapted scale appears suitable for assessing family dynamics in this specific population. Further research should confirm these findings in broader populations.